A2AR‐induced transcriptional deregulation in astrocytes: An in vitro study. Issue 12 (22nd July 2019) - Paiva, Isabel; Carvalho, Kévin; Santos, Patrícia; Cellai, Lucrezia; Pavlou, Maria Angeliki S.; Jain, Gaurav; Gnad, Thorsten; Pfeifer, Alexander; Vieau, Didier; Fischer, André; Buée, Luc; Outeiro, Tiago F.; et al.
Abstract: Adenosine A2A receptors (A2A R) are modulators of various physiological processes essential for brain homeostasis and fine synaptic tuning. In certain neurodegenerative conditions, notably Alzheimer's disease (AD), A2A Rs are pathologically upregulated in neurons but also in astrocytes. In that context, the use of A2A Rs inhibitors, normalizing impaired receptor function, is seen as a potential therapeutic strategy. However, the impact of A2A R alterations, particularly in astrocytes, is not fully understood. Here, we investigated the effect of A2A R overexpression on transcriptional deregulation in primary astrocytic cultures. By performing whole transcriptome analysis, we found that A2A R overexpression promotes robust transcriptional changes, mostly affecting immune response, angiogenesis, and cell activation‐related genes. Importantly, we observed that treatment with SCH58261, a selective A2A R antagonist, restored the expression levels of several inflammatory and astrocytic activation‐related genes, such as Interleukin‐1beta and vimentin. This supports the notion that A2A R blockade could restore some astrocytic dysfunctions associated with abnormal A2A R expression, further arguing for a potential beneficial impact of receptor antagonists in A2A R‐induced transcriptional deregulation, inflammation, and astrogliosis. Overall, our findings provide novel insights into the putative impact of A2A R overexpression on transcriptional deregulation in astrocytes, thereby opening novel avenues for the use of A2A R antagonists as potential therapeutic strategy in neurodegenerative diseases. Main Points: A2AR overexpression induces transcriptional alterations in inflammatory and secretion associated pathways in astrocytes. A selective adenosine A2AR antagonist corrects transcriptional alterations associated with A2AR overexpression in astrocytes.